Let's pretend - MacDonald, Amy.; Roffey, Maureen (Cambridge, Mass. : Candlewick Press, 1994)
Readers are encouraged to pretend to act like various animals. On board pages.
Mode of access: Internet.
Keywords: Imagination -- Fiction; Animals -- Fiction